Hotspot development and shading response of shingled PV modules. (1st September 2020) - Clement, Carlos Enrico; Singh, Jai Prakash; Birgersson, Erik; Wang, Yan; Khoo, Yong Sheng
Highlights: Shingled modules develop higher hotspot temperatures than conventional configurations such as half-cell modules. Non-uniformities in shingled cells lead to variations in shading response. Secondary hotspot sites may develop in parallel strings even without any shading. Abstract: The shingled architecture has gained attention in recent years for its improved packing density and reduced ohmic losses that have led to greater module efficiencies. In the photovoltaics industry where land and auxiliary costs scale with area utilization, shingling is a promising emergent technology. However, because current designs use smaller cell areas and upwards of 34 cell strips in series per string, shingled modules are vulnerable to hotspots, particularly due to smaller shading elements. In this work, we experimentally characterize the hotspot and power response of shingled modules. Two operating scenarios are considered, simulating both utility scale systems and standardized testing conditions. We report maximum hotspot temperatures of 145 °C at partial shading and show how non-uniformities in the cell properties lead to variations in module shading response and hotspot temperature. Furthermore, we observe that shingled modules develop higher hotspot temperatures than conventional half-cell modules. Finally, we demonstrate how unshaded parallel strings in a shingled module can concurrently develop minor hotspots at the onset of bypass diode activation.